The mobilization of families of the desaparecidos in Argentina and Mexico: between state terrorism and criminal violence (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
This contribution aims to analyse, through a historical-social perspective, the trajectory, the most important moments, and the impact of the mobilization of the victims’ relatives of enforced disappearances in two different socio-political contexts but characterized by the systematic use of violence: the military dictatorship in Argentina (1976-1983), with a focus also on the subsequent democratic period, and the “War on drugs” in Mexico (2006-2018).
Keywords: enforced disappearances; violence; social mobilization; relatives of victims; human rights